The influence of birth quartile, maturation, anthropometry and physical performances on player retention: Observations from an elite football academy. Issue 2 (April 2020) - Patel, Rickesh; Nevill, Alan; Smith, Tina; Cloak, Ross; Wyon, Matthew
Understanding the factors that influence player retention within elite youth football can be used to enhance current practices. This study investigated an English Category 1 academy to determine if birth quartile, somatic maturity, anthropometric and physical performance characteristics are associated with player retention across the developmental pathway. Birth dates of 355 elite players from Under 11 (U11) to U21 groups were categorised into birth quartiles, and logistic regression (odds ratio) analysis was used to determine the differences in retention. Multilevel modelling compared somatic maturity, anthropometry, countermovement jump, sprint time (10 and 30 m), agility T-test and Yo-Yo Intermittent Recovery Level 1 or 2 performance between retained and dropout players. Logistic regression (odds ratio) analysis revealed no significant differences between birth quartiles for the likelihood of being retained across age groups. Multilevel modelling revealed that retained players were typically older, advanced in maturity and superior in body size and physical performances compared to dropouts, with small to medium effect sizes typically observed. This study indicates that within a highly selective cohort of young football players, somatic maturity, anthropometric and physical performance characteristics, but not birth quartile, distinguish individuals that are subsequently retained or dropout in an age group-dependent manner. Youth football organisations should seek to implement multidisciplinary and dynamic talent selection and retention strategies to prevent inappropriate discrimination and loss of talented young players.